Distinctive clinicopathological features of adenocarcinoma in situ and minimally invasive adenocarcinoma of the lung: A retrospective study. (March 2019) - Ishida, Hironori; Shimizu, Yoshihiko; Sakaguchi, Hirozo; Nitanda, Hiroyuki; Kaneko, Koichi; Yamazaki, Nobuhiro; Yanagihara, Akitoshi; Taguchi, Ryo; Sakai, Fumikazu; Yasuda, Masanori; Kobayashi, Kunihiko
Highlights: WHO defined AIS and MIA as early phases of lung adenocarcinoma in 2015. Patients with MIA, compared to those with AIS are more likely to be male. Ki-67 labeling index for cell proliferative activity distinguishes MIAs from AIS. MIAs have more EGFR mutations, with a higher exon 19 to 21 mutation ratio than AIS. Distinguishing AIS from MIA is apt despite the same good outcomes after resection. Abstract: Objectives: The aim of this study was to investigate distinguishing clinicopathological features, in addition to histological invasiveness, in adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) of the lung. Materials and methods: Patients with lung adenocarcinoma who underwent surgery at our hospital between 2007 and 2014 were reviewed, focusing on computed tomography (CT) images, operative procedures and clinical outcomes, histopathology, Ki-67 immunostaining, and EGFR -mutation status. EGFR mutations were examined using a peptide nucleic acid–locked nucleic acid PCR clamp method. Group comparisons were investigated by Mann–Whitney U or Fisher's exact tests. Results: Of 629 patients with lung adenocarcinoma who underwent surgery, 91 (14%) of 103 AIS (n = 34) or MIA (n = 69) tumors were reviewed. The ratio of male to female patients with MIA compared to AIS was significantly higher ( p < 0.02). Of 103 tumors, 99 (96%) were non-mucinous. By CT, 74% of AIS appeared as pure ground-glass nodules and 75% of MIAs as part-solid ground-glass nodules. Pathological tumor diameters and Ki-67 labeling index (LI) values were significantly greater for MIAs compared to AIS ( p < 0.001 for both). A Ki-67 LI of ≥2.8% indicated the presence of an MIA rather than an AIS. EGFR mutations were more frequently detected in MIAs (33/69, 48%) than AIS (9/34, 26%; p = 0.055). The ratio of exon 19 deletions to exon 21 missense mutations in MIAs tended to be higher than those in AIS ( p = 0.06). Patients did not experience a local recurrence or metastasis after AIS and MIAs were removed by wedge resection, segmentectomy or lobectomy. Five-year recurrence-free survival rates were 100%. Conclusion: Despite similar surgical outcomes for AIS and MIAs, we found differences in terms of gender, tumor diameters, CT findings, Ki-67 LI and a subset of EGFR mutations, highlighting the validity of classifying the two subtypes.